Feeding Practices and Influencing Factors in Mothers of Children Under 24 Months with Gastrointestinal Disorders: A Cross Sectional Study - Wazir, Hakim Ullah; Naz, Sadaf; Inam, Noora; Humaira; Inayat Ullah; Muhammad Farhan Rasool; Dad, Ali (Indus Journal of Bioscience Research, 2025)
Introduction: Proper feeding practices play a vital role in a child’s growth, development, and recovery during illness. Breastfeeding and timely introduction of complementary foods are essential to prevent malnutrition and reduce childhood morbidity and mortality, particularly from gastrointestinal illnesses such as diarrhea. Inappropriate feeding during or after illness can worsen nutrient deficiencies and delay recovery. Promoting optimal feeding practices among mothers is therefore crucial for improving child health outcomes, especially in developing regions. Objectives: To estimate the prevalence of appropriate feeding practices in children with gastrointestinal disorders. To describe the types and frequencies of early feeding practices in children with gastrointestinal disorders. To identify maternal factors associated with appropriate feeding practices in children with gastrointestinal disorders. Methods: This descriptive cross-sectional study was conducted from August to November in the paediatric wards of Bacha Khan Medical Complex, Swabi, Pakistan, using self-structured questionnaires. Results: A total of 160 mother-child pairs participated, with exclusions for severe illness or incomplete responses. Overall on average 47.8% of the mothers properly practiced breastfeeding, complementary foods and feeding practices during illness. Key findings included 16.9% starting breastfeeding within 1 h, 14.4% giving breast-milk first, 65% timely weaning, 88.8% breastfeeding during illnesses, and 53.8% adding complementary foods during illness. Conclusion: Most respondents practiced poor early feeding, except those properly counselled. Mothers who were not counselled by doctors during the illness also practiced poor feeding. Prenatal and postnatal counselling is crucial for good feeding practices.